Development of E-Module Learning Media on Android-Based Alternating Current Materials to Improve Student's Critical Thinking Ability - Titin Oktavia (CV Media Inti Teknologi, 2022)
This study aims to determine the feasibility perception of the development of android-based e-module learning media. This research is a continuation of previous research, which is limited to the analysis stage. The research method used is descriptive and is part of research and development (RnD) with the ADDIE model. This media consists of concept maps, material descriptions, learning videos, worksheets, and practice questions that are packaged in such a way that students can be more active in the learning process in class. The research instrument used was a validation sheet consisting of validation by material experts, media experts and linguists. The results of expert validation obtained a percentage of 84% and the results of student perceptions obtained a percentage of 82% in other words this e-module is feasible to use.